TARIF PAJAK, PROBABILITAS PEMERIKSAAN PAJAK DAN TINGKAT KEPATUHAN PAJAK: SEBUAH STUDI EKSPERIMEN - Ricky Rudianto, Nur Ahmad (Fakultas Ekonomi dan Bisnis Islam, 2018)
This study examines the tax rates and probability of tax examination on taxpayer compliance. Based on experimental 2x2 factorial design data between subjects, participants given low tax rates manipulations tend to be more compliant than participants given high tax rates manipulations, as well as the probability of tax examination, participants tend to be more compliant on high probability of tax examination manipulation than low probability of tax examination manipulation. Lastly, the interaction effect results do not show significant results. It was found that tax compliance can be achieved more effectively when low tax rates combined with high probability of tax examination. This study contributes to the tax compliance literature especially with the specific topic of tax rates and Probability of tax examination.